Three-dimensional modelling of composite frames with ductile connections in fire. (February 2022) - Liu, Yu; Huang, Shan-Shan; Burgess, Ian
Abstract: Connections are vital to the survival of steel and composite framed structures in fire. To prevent brittle failure of connections at elevated temperatures, a novel connection with high ductility has been proposed previously. In this paper, the fire performance of this ductile connection in composite frames is investigated. In order to consider the influence of the out-of-plane structural behaviour, the 3-D models of a fire compartment of a typical composite framed structure with different connection types, including the ductile connection, idealised rigid and pinned connections, as well as commonly used end-plate and web-cleat connections have been built using Vulcan to compare the performance of ductile connection with other connection types. Comparison results show that the proposed ductile connection can provide additional ductility within composite frame to accommodate the axial deformation of connected beam at high temperatures. To further save computational costs, the 3-D composite frame compartment model has been reduced to a quarter of its original size by using symmetric boundaries. The influence of unconnected length between the slab and beam on the connection performance has also been investigated. It is found that the relative beam end slip is affected by the unconnected length. However, due to the inherent mechanical properties of the ductile connection, the influence of unconnected length on the force of the ductile connection is negligible, which can also reflect the deformation capacity of ductile connection.